Influência da temperatura de formação do íon de Keggin no processo de pilarização de esmectitas - GUERRA, Denis de Jesus Lima (2012)
Clays pillared with Keggin ions (AL-PILC) have been synthesized at OH/Al=2 molar ratio and various pretreatment temperatures (ambient temperature to 105ºC) in order to determine the optimum preparation conditions of the pillaring agent (Al13). The evolution of basal spacing, FTIR spectra, TG-curves, surface area and pillars number in function of temperatures of Al13 formation were studied. It was observed an increase number pillars and surface area at low temperatures.